Gesture Recognition: A Communication and Future to Tablets (International Journal of Engineering and Computer Science, 2013)
The term “Gesture” means non-verbal communication by means of visible body actions in order to communicate a particular message, similarly “gesture recognition” is a field of computer science technology which aims at recognizing human gestures in order to convey a particular instruction by means of mathematical algorithms. Gesture recognition is an initiative from the technology’s end in order to understand human perspective through sign language. The algorithm basically aims to determine “what instruction is to be given by the human being at a particular instant”. Human gesture is approximated with somewhat close to the actual instruction which is indeed in the person’s mind at that point of time. That is “the gesture should resemble the instruction which is to be given by the human to the machine “. This reduces human complexity.